Paving the way for methane hydrate formation on metal–organic frameworks (MOFs) - Casco, Mirian E. (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
The presence of a highly tunable porous structure and surface chemistry makes metal–organic framework (MOF) materials excellent candidates for artificial methane hydrate formation under mild temperature and pressure conditions (2 °C and 3–5 MPa). Experimental results using MOFs with a different pore structure and chemical nature (MIL-100 (Fe) and ZIF-8) clearly show that the water–framework interactions play a crucial role in defining the extent and nature of the gas hydrates formed. Whereas the hydrophobic MOF promotes methane hydrate formation with a high yield, the hydrophilic one does not. The formation of these methane hydrates on MOFs has been identified for the first time using inelastic neutron scattering (INS) and synchrotron X-ray powder diffraction (SXRPD). The results described in this work pave the way towards the design of new MOF structures able to promote artificial methane hydrate formation upon request (confined or non-confined) and under milder conditions than in nature.